STRATEGI MENENTUKAN KOMPONEN INDIKATOR DAN TOLAK UKUR KINERJA BELANJA LANGSUNG BIDANG SOSIAL UNTUK JANGKA MENENGAH PADA APBD - Akmal, Akmal (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2012)
This article examines the method to determine indicators and benchmarks of the performance of mid-term direct social expenses of the local administration’s budget. Indicators here refer to the means to plan and help communication process. Indicators are used for social evaluation in finding out the needs and priorities of the communities’ social rights in the development. The components of the social indicators include ideological social aspect, political social aspect, economical social aspect, cultural social aspect, and security social aspect. Keywords: strategy, local administration’s budget, direct expenses’ performance indicators